Majelis Ta’lim Sebagai Alternatif Pusat Pendidikan Islam (Studi Kasus pada Majelis Ta’lim Se Kecamatan Natar Lampung Selatan) - Arif Mustopa (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2016)
In the public, living we see routine activities what is done. The routine activities are religious and non religious. Usually, religious activities are done in majelis ta’lim. Majelis ta’lim that grow in the community can to became alternative for central of islamic education if the managed well. Therefore, the author want to discuss about this issue with expectation to know of factors that cause the failure religious building in majelis ta’lim especially in Natar, so to know activities that required to done so as really became alternative for central of Islamic education. This research is quantitative research with collecting data from majelis ta’lim which became this research object. The collecting data is done with instruments: as observation, interview, and documentation. From this research, we can know that style and methode is done by the teacher is principal key to success in majelis ta’lim. Therefore, the inovation is required in majelis ta’lim activities so that can interest of more pilgrims and make him the alternative for central of Islamic education.